Research on the Efficiency Evaluation of Company A's Financial Shared Service Center - Song, Caiyu (Asia Pacific Economic and Management Review, 2025)
Against the backdrop of the widespread global application of financial shared services and domestic policies driving enterprises' digital transformation, Company A, an enterprise in the energy industry, established a Financial Shared Service Center (FSSC) in 2016 to address issues such as inconsistent accounting, cumbersome processes, and weak risk control in the traditional decentralized financial model. Adhering to the principles of comprehensiveness, systematicness, goal-orientation, and feasibility, this paper combines the Analytic Hierarchy Process (AHP) to establish an evaluation framework consisting of 4 first-level indicators ("Strategic Planning", "Information System", "Organizational Personnel", and "Process Management") and 16 second-level indicators. After scoring by over 10 experts from Company A, constructing a judgment matrix, and conducting a consistency test (all CR values < 0.1), it is determined that "Process Management" and "Information System" have relatively high weights, while indicators such as "Process Effectiveness" are core second-level indicators. The study finds that only the "Strategic Planning" dimension of Company A's FSSC meets the standards, while there are shortcomings in the three dimensions of "Information System" (e.g., subpar system efficiency), "Organizational Personnel" (e.g., insufficient personnel management quality), and "Process Management" (e.g., imbalanced process effectiveness). Based on this, optimization proposals are put forward from three aspects: information system integration, improvement of organizational personnel assessment and incentives, and process reconstruction with risk control. These proposals provide references for the improvement of Company A's FSSC and similar practices in the energy industry.